Contrast-Enhanced MR Angiography Is Not More Accurate Than Unenhanced 2D Time-of-Flight MR Angiography for Determining ≥70% Internal Carotid Artery Stenosis - Babiarz, L.S.; Romero, J.M.; Murphy, E.K.; Brobeck, B.; Schaefer, P.W.; González, R.G.; Lev, M.H. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Internal carotid artery (ICA) atheromatous disease is an important cause of ischemic stroke, and endarterectomy or stent placement is typically indicated for symptomatic patients with ≥70% stenosis. Our purpose was to compare contrast-enhanced MR angiography (CE-MRA) with unenhanced 2D time-of-flight MR angiography (2D TOF MRA) in detecting hemodynamically significant ICA stenosis, by using CT angiography (CTA) as the reference standard.MATERIALS AND METHODS: This was an institutional review board−approved retrospective study. We identified 177 consecutive patients (354 ICAs) who received correlative CE-MRA, 2D TOF MRA, and CTA. Two neuroradiologists blinded to the CTA data graded the degree of ICA stenosis according to a 5-point scale. Additionally, luminal signal-intensity characteristics including 1) signal intensity drop-out, 2) distal-vessel narrowing, and 3) distal-vessel signal-intensity reduction were recorded. MRA results were correlated with those of CTA, and receiver-operating-characteristic (ROC) curves were constructed.RESULTS: On CTA, there were 55 ICAs with and 299 without ≥70% stenosis. CE-MRA was 84% sensitive and 96% specific for detecting ≥70% stenosis; 2D TOF MRA was 80% sensitive and 95% specific. The area under the ROC curve was 0.97 for CE-MRA and 0.95 for 2D TOF MRA (P = .51, not significant). For both MRA studies, each of the luminal signal-intensity characteristics had high specificity (>98%) but poor-to-mild sensitivity (35%–66%) in detecting ≥70% stenosis.CONCLUSIONS: Although it is established that CE-MRA more accurately delineates neurovascular anatomy than does unenhanced 2D TOF MRA, the administration of gadolinium did not offer a significant advantage in distinguishing surgically treatable ICA stenosis. This conclusion may be important in patients with contraindications to gadolinium.